Pemberdayaan Masyarakat Dalam Pembuatan Larvitarp dan Pemasangannya Sebagai Upaya Menurunkan Populasi Nyamuk Aedes Aegypti di Kelurahan Manggala, Kota Makssar - Nur Haidah; Sulasmi; Juherah (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Mechanical mosquito population control can use Trapping. Trapping is a mosquito trap as an effort to reduce the mosquito population in an effort to reduce the mosquito population that causes dengue by using attractant media. An attractant is something that has an attraction to insects (mosquitoes) both chemically and physically. Chemical attractants can be in the form of ammonia, CO2, lactic acid and actenol compounds. These substances or compounds are made from organic materials or are the result of metabolic processes of living things which have been shown to affect the olfactory nerves of the Aedes aegypti mosquito.Modification of the trapping form and the use of attractant types with the right concentration ratio are needed to produce an Aedes aegypti mosquito vector trap that can work optimally, is easy to do and can be applied in the field. The results of previous studies suggest using dry media to make it easier to apply and be applied directly in the field. Through the One House One Jumantik Movement, the target participants of this community service activity are PKK cadres and larvae monitors at the RT level to mobilize housewives in monitoring the presence of larvae at home. The knowledge of the target audience was assessed through pre and post tests which were distributed during the event. In accordance with the results of the pre and post test recapitulation, it is known that the target already has sufficient knowledge so that the increase in the percentage of knowledge after explaining the material increases by 5 percent. The enthusiasm of the target in the practice of making larvitrap can explain that the curiosity and intention of the target in an effort to suppress dengue cases is high. In addition to making larvitrap, the target was also given information about the identification and bionomic vector of DHF through a microscope. Through a microscope, the target will know the true description of Aedes aegypti mosquito larvae that are different from other types of mosquito larvae.